PENGARUH KONSENTRASI SERTA PENAMBAHAN GLISEROL TERHADAP KARAKTERISTIK FILM ALGINAT DAN KITOSAN - Giovanni Anward; Yusuf Hidayat; Nur Rokhati (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2013)
Bioethanol used as fuel should have purity greater than 99.5%, but the conventional distillation produces only 95% purity. One way to increase the purity of ethanol is pervaporation method using selective membrane. The aim of this research is to prepare and characterize alginate and chitosan films. To determine the optimum concentration of alginate and chitosan films, both of these films were characterized. The results showed that the optimum alginate film obtained at 3% of concentration with the addition of 20% glycerol, while the optimum chitosan film obtained at 3% of concentration without the addition of glycerol. Alginate film has the highest permeability and swelling degree, while chitosan film has the lowest value. Alginate and chitosan films have the highest swelling degree in water, then 95% alcohol and the lowest is in PA alcohol.